The pretext of inflation. The german policy of cuts prioritizing the creditor - de la Pola Zurita, José Carlos (Papeles de Europa, 2012)
Under the subterfuge of inflation and by means of a strict conditionality in return forproviding financial assistance to peripheral Europe, Germany is trying to consolidatean austerity policy that guarantees the payment of debts to German banks. The cutsimposed by Berlin, however, increase the risk of recession and intensify the North-South divide in Europe.
Keywords: Germany; European Central Bank; Eurozone; Spain; Greece; Austerity